“Quality not Quantity”: The Role of the Editor and the Language Consultant in the English Translations of Swedish and Norwegian Children’s Fiction at Turton & Chambers, 1988–92 - Berry, Charlotte (Mémoires du livre / Studies in Book Culture, 2017)
This article takes as its subject the project of British author and editor Aidan Chambers to set up a small press dedicated to publishing modern European children’s literature in translation, 1988–92. Positioned within Gideon Toury’s framework of Descriptive Translation Studies, this paper outlines the history of the firm and its founding ideology to publish children’s literature “with a difference” for a British audience. As a result, preliminary norms (relating to text, author and translator selection) and operational norms (relating to translation strategies) for four novels by Maud Reuterswärd, Peter Pohl and Tormod Haugen are identified and analyzed. Fundamental to the article’s methodology is the use of bibliographical, archival and oral history primary sources. The principal focus of research interest is Chambers’ use of language consultants in addition to his commissioned translators in an unusual and sometimes challenging professional collaboration of editor-translator-consultant within a Nordic-British setting.